Factors affecting the ethical judgment of business ethics’ students - Ismail, Suhaiza; Mohd Redza, Zaza Eliza (UiTM Terengganu, 2013)
Purpose: The main objective of this study is to examine the factors that affect the ethical judgment of Business Ethics students. The factors are year of study, gender, academic major, overall academic performance and Business Ethics result. Design/methodology/approach: A questionnaire survey was administered to 209 students taking Business Ethics course in a higher learning institution in Malaysia. Ethical vignettes obtained from Emerson and Conroy (2004) were used to capture how students evaluate the ethical behaviour depicted in the vignettes. A multiple regression analysis revealed that Business Ethics result and year of study are factors that have a significant effect on the ethical judgment of students. Findings: The study reveals that Business Ethics result and year of study are significant factors that affect the ethical judgment of the students. Practical implications: The findings of this study may assist accounting practitioners and future employers in recruiting prospective employees. Employers may want to emphasis the significant factors in the hiring process future employees to ensure that the employees they employ have an appropriate level of ethical behaviour. Keywords: Ethical judgment, Business Ethics, year of study, gender, academic major, performance